Effect of piperazine on CO2 loading in aqueous solutions of MDEA at low pressure - Ali, B.S.; Aroua, M.K. (International Journal of Thermophysics, 2004)
Solubilities of CO2 in aqueous solutions of activated methyldiethanolamine (MDEA) has been investigated for temperatures and CO 2 partial pressures ranging from 40 to 80Â°C and 0.1 to 100 kPa, respectively. Piperazine (PZ) is used as activator, with a concentration ranging from 0.01 to 0.1 M, keeping the amine total concentration in the aqueous solution at 2 M. The experimental solubility results were represented by the mole ratio of CO2 per activated amine present in the liquid mixture. The addition of piperazine, as activator for MDEA, increased the solubility of CO2 in the region of low CO2 partial pressure compared to pure MDEA. The CO2 loading increased with decreasing temperature, increasing CO2 partial pressure, and increasing PZ concentration.